Negative electrode material, negative electrode plate and lithium ion battery

By designing a negative electrode material in a lithium-ion battery, combining the aspect ratio of the first and second negative electrode active materials and the powder compaction pressure relief rebound rate, controlling the particle size and oxygen content, the energy density and electricity of the lithium-ion battery are solved. The problem of core fluctuation liquid achieves a balance between high energy density and safety performance.

CN119170766APending Publication Date: 2024-12-20ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411246326.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Lithium-ion batteries have shortcomings in terms of energy density and fast charging capabilities, especially the design and cycle life of the negative electrode materials, which leads to the battery cell liquid surge, affecting the battery performance and packaging.

Method used

Using a negative electrode material, including the first and second negative electrode active materials, by controlling the relationship between its aspect ratio and the rebound rate of powder compaction pressure relief, the pores and compaction density between particles after rolling are ensured, and the compaction density is increased. The permeability of the electrolyte reduces the battery cell fluctuation, while controlling the particle size and surface oxygen content to balance energy density and safety.

Benefits of technology

The energy density improvement of lithium-ion batteries and the solution to the battery cell liquid fluctuation problem has been achieved, ensuring the safety performance and good thermal stability of the battery under high energy density, and reducing the safety risks caused by overheating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005030872350000081
    Figure BDA0005030872350000081
  • Figure BDA0005030872350000091
    Figure BDA0005030872350000091
  • Figure BDA0005030872350000101
    Figure BDA0005030872350000101
Patent Text Reader

Abstract

The invention discloses a negative electrode material, a negative electrode plate and a lithium ion battery. The negative electrode material comprises a first negative electrode active material and a second negative electrode active material, the length-diameter ratio of the first negative electrode active material is a, and the powder compaction pressure relief rebound rate is P1; the length-diameter ratio of the second negative electrode active material is b, and the powder compaction pressure relief rebound rate is P2; p1, P2, a and b satisfy the relationship: (37 * P1 / a + 75 * P2 / b) > 2.5. According to the invention, the length-diameter ratio of the first negative electrode active material and the second negative electrode active material and the powder compaction pressure relief rebound rate are controlled to meet the relational expression: (37 * P1 / a + 75 * P2 / b) > 2.5, so that the relationship between the length-diameter ratio of the material and the powder compaction pressure relief rebound rate is balanced; and electrolyte permeation is increased while pores and compaction density among the rolled negative electrode active material particles are ensured, and battery cell liquid expansion is reduced, so that the problem of battery cell liquid expansion is solved while the energy density of the lithium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of secondary batteries, and in particular to a negative electrode material, a negative electrode sheet and a lithium ion battery. Background Art

[0002] At present, lithium-ion batteries are widely used in various digital products and power battery fields due to their high energy density. With the growing demand for fast charging technology in digital products, higher and higher requirements are placed on the energy density and fast charging capacity of lithium-ion batteries. In particular, there are some technical problems that have not yet been fully resolved in the design and function of negative electrode materials.

[0003] Negative electrode materials play a vital role in lithium-ion batteries, and their performance directly affects the energy density, charging speed and cycle stability of the battery. Traditional negative electrode materials are mainly graphite, which is widely used due to its good electrochemical stability and high electronic conductivity. However, the low gram capacity of graphite materials limits its application potential under high energy density requirements. Although other types of negative electrode materials have higher gram capacities, such as silicon-carbon and silicon-oxygen materials, the cycle life and expansion of these materials have yet to be solved. The key to improving energy density is to improve the compaction level and capacity of the electrode. However, the improvement in the compaction level is often accompanied by the problem of electrolyte penetration, which will make it difficult to retain the electrolyte in the battery cell. The electrolyte is free on the periphery of the battery cell, causing the battery cell to swell too thickly and unable to meet the battery packaging. Balancing energy density and swelling issues is the key to the development of the lithium battery industry.

[0004] In view of these problems, there is an urgent need to develop an innovative technical solution that can not only improve the energy density of lithium-ion batteries but also solve the problem of battery cell swelling. Summary of the invention

[0005] The purpose of the present invention is to provide a negative electrode material that can improve the energy density of lithium-ion batteries and solve the problem of battery cell liquid swelling in view of the shortcomings of the prior art.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A negative electrode material, comprising a first negative electrode active material and a second negative electrode active material;

[0008] The aspect ratio of the first negative electrode active material is a, and the powder compaction pressure release rebound rate is P1; the aspect ratio of the second negative electrode active material is b, and the powder compaction pressure release rebound rate is P2; wherein P1, P2, a and b satisfy the relationship: 37*P1 / a+75*P2 / b>2.5.

[0009] This relationship is used to balance the relationship between the aspect ratio of the material and the powder compaction pressure relief rebound rate, ensuring the pores and compaction density between the negative electrode active material particles after roller pressing while increasing the electrolyte penetration and reducing the cell swelling to achieve high energy density and good battery performance. Materials with a larger powder compaction pressure relief rebound rate can provide a certain elastic recovery after roller pressing, which helps to buffer the pressure during the compaction process of the pole piece, maintain the pores between the particles, increase the permeability of the electrolyte, and thus reduce the battery swelling phenomenon. A larger powder compaction pressure relief rebound rate may cause the cell to become thicker, which will reduce the energy density of the battery.

[0010] Preferably, the aspect ratio a of the first negative electrode active material is 1<a≤3.

[0011] Preferably, the aspect ratio b of the second negative electrode active material is 3≤b<5.

[0012] Among them, particles with a larger aspect ratio are easier to extend and slide during rolling, which helps to achieve a higher compaction density. This particle shape is conducive to improving the energy density of the battery. Particles with a smaller aspect ratio are more round in shape, which can provide a certain support during the compaction process and help maintain the stability of the structure.

[0013] Preferably, the powder compaction pressure relief rebound rate P1 of the first negative electrode active material is 10%-15%, and the powder compaction pressure relief rebound rate P2 of the second negative electrode active material is 6%-10%. Materials with a larger powder compaction pressure relief rebound rate can provide a certain elastic recovery after rolling, which helps to buffer the pressure during the compaction of the pole piece, maintain the pores between the particles, increase the permeability of the electrolyte, and thus reduce the battery swelling phenomenon. However, a larger powder compaction pressure relief rebound rate may cause the battery cell to become thicker, which may reduce the energy density of the battery. Preferably, the particle size of the first negative electrode active material is Dv50, and the surface oxygen content is H1; the particle size of the second negative electrode active material is Dv′50, and the surface oxygen content is H2, and the mass of the second negative electrode active material accounts for the total mass of the negative electrode material k; wherein Dv50, Dv′50, H1, H2 and k satisfy the relationship: H1*Dv50+235k*H2 / Dv50<1.85.

[0014] This relationship is used to balance the energy density and hot box performance of the battery. The surface oxygen content of the first negative electrode active material cannot be too large, and the proportion and surface oxygen content of the second negative electrode active material must be controlled to ensure that the battery has high energy density while also having good thermal stability and safety. A high oxygen content means a deep degree of etching, which can increase the gram capacity and compaction density of the material, but it may also lead to more side reactions and affect the safety of the battery. A high degree of etching plus a small particle size of the second negative electrode active material may cause the thermal stability of the battery to deteriorate, so it is necessary to balance energy density and safety during design.

[0015] Preferably, the mass of the second negative electrode active material accounts for 10%-30% of the total mass k of the negative electrode material.

[0016] Preferably, the content k of the second negative electrode active material is 10%-30% of the total content of the negative electrode active material. Preferably, the surface oxygen content H1 of the first negative electrode active material is 5%-10%, and the surface oxygen content H2 of the second negative electrode active material is 0%-3%. The surface oxygen content reflects the degree of oxidation etching of the material. Oxidation etching can improve the capacity and compaction level of the material, increase the specific surface area of ​​the material, and thus improve the performance of the battery. The etching process also affects the surface roughness of the material, further affecting the electrochemical performance of the battery.

[0017] Preferably, the particle size Dv50 of the first negative electrode active material is 10-16 μm, and the particle size Dv′50 of the second negative electrode active material is 6-10 μm.

[0018] Preferably, the negative electrode active material includes one or more of natural graphite and artificial graphite.

[0019] In addition, the present invention also provides a negative electrode sheet, comprising the negative electrode material mentioned above.

[0020] In addition, the present invention also provides a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator spaced between the positive electrode sheet and the negative electrode sheet, wherein the negative electrode sheet is the above-mentioned negative electrode sheet.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1) The present invention controls the aspect ratio of the first negative electrode active material and the second negative electrode active material and the powder compaction pressure relief rebound rate to satisfy the relationship: (37*P1 / a+75*P2 / b)>2.5, which is used to balance the relationship between the aspect ratio of the material and the powder compaction pressure relief rebound rate, ensure the pores and compaction density between the negative electrode active material particles after rolling, increase the electrolyte penetration, and reduce the cell swelling, so as to improve the energy density of the lithium-ion battery and solve the cell swelling problem at the same time.

[0023] 2) The present invention controls the particle size and oxygen content of the first negative electrode active material and the second negative electrode active material to satisfy the relationship: (H1*Dv50+235k*H2 / Dv50)<1.85, which is used to balance the relationship between the particle size and oxygen content of the materials, thereby ensuring that the battery has high energy density while also having high safety performance, reducing safety risks caused by problems such as battery overheating. DETAILED DESCRIPTION

[0024] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.

[0025] According to a first aspect of the present application, the present application aims to provide a negative electrode material, comprising a first negative electrode active material and a second negative electrode active material;

[0026] The aspect ratio of the first negative electrode active material is a, and the powder compaction pressure release rebound rate is P1; the aspect ratio of the second negative electrode active material is b, and the powder compaction pressure release rebound rate is P2; wherein P1, P2, a and b satisfy the relationship: (37*P1 / a+75*P2 / b)>2.5.

[0027] In some embodiments, the aspect ratio a of the first negative electrode active material is 1<a≤3, for example, 1.1, 1.3, 1.6, 1.9, 2.1, 2.3, 2.6, 2.9, or 3.

[0028] In some embodiments, the aspect ratio b of the second negative electrode active material is 3≤b<5, for example, 3, 3.1, 3.3, 3.6, 3.9, 4.1, 4.3, 4.6, or 4.9.

[0029] In some embodiments, the powder compaction pressure relief rebound rate P1 of the first negative electrode active material is 10%-15%, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%; the powder compaction pressure relief rebound rate P2 of the second negative electrode active material is 6%-10%, for example, it can be 6%, 7%, 8%, 9%, 10%.

[0030] In some embodiments, the particle size of the first negative electrode active material is Dv50, and the surface oxygen content is H1; the particle size of the second negative electrode active material is Dv′50, and the surface oxygen content is H2; wherein Dv50, Dv′50, H1 and H2 satisfy the relationship: (H1*Dv50+235k*H2 / Dv50)<1.85.

[0031] In some embodiments, the mass of the second negative electrode active material accounts for 10%-30% of the total mass k of the negative electrode material, for example, 10%, 15%, 20%, 25%, or 30%.

[0032] In some embodiments, the surface oxygen content H1 of the first negative electrode active material is 5%-10%, for example, it can be 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%; the surface oxygen content H2 of the second negative electrode active material is 0%-3%, for example, it can be 0%, 1%, 2%, 3%.

[0033] In some embodiments, the particle size Dv50 of the first negative electrode active material is 10-16μm, for example, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm; the particle size Dv′50 of the second negative electrode active material is 6-10μm, for example, 6μm, 7μm, 8μm, 9μm, 10μm.

[0034] In some embodiments, the negative electrode active material includes one or more of natural graphite and artificial graphite.

[0035] According to a second aspect of the present application, the present application provides a negative electrode sheet comprising the above-mentioned negative electrode material.

[0036] According to a third aspect of the present application, the present application provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, wherein the negative electrode sheet is the negative electrode sheet described above.

[0037] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material. The positive electrode active material may include but is not limited to a chemical formula such as Li a Ni x Co y M z O 2-b N b (where 0.95≤a≤1.2, x>0, y≥0, z≥0, and x+y+z=1, 0≤b≤1, M is selected from a combination of one or more of Mn and Al, and N is selected from a combination of one or more of F, P, and S), the positive electrode active material may also be, but is not limited to, LiCoO2, LiNiO2, LiVO2, LiCrO2, LiMn2O4, LiCoMnO4, Li2NiMn3O8, LiNi 0.5 Mn 1.5O4, LiCoPO4, LiMnPO4, LiFePO4, LiNiPO4, LiCoFSO4, CuS2, FeS2, MoS2, NiS, TiS2, etc. The positive active material may also be modified. The method of modifying the positive active material should be known to those skilled in the art. For example, the positive active material may be modified by coating, doping, etc. The material used for the modification may include but is not limited to a combination of one or more of Al, B, P, Zr, Si, Ti, Ge, Sn, Mg, Ce, W, etc. The positive current collector is usually a structure or part for collecting current. The positive current collector may be various materials suitable for use as a positive current collector for lithium-ion batteries in the art. For example, the positive current collector may include but is not limited to metal foil, etc., and more specifically may include but is not limited to aluminum foil, etc.

[0038] The separator can be any material suitable for secondary battery separators in the art, for example, it can be a combination of one or more of, but not limited to, polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.

[0039] The lithium-ion battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt and an additive. Among them, the electrolyte lithium salt can be LiPF6 and / or LiBOB used in high-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, and LiPF6 used in low-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, LiPF6, and LiTFSI used in anti-overcharge electrolytes; it can also be at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. The organic solvent can be a cyclic carbonate, including PC and EC; it can also be a chain carbonate, including DFC, DMC, or EMC; it can also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to at least one of film-forming additives, conductive additives, flame retardant additives, anti-overcharge additives, additives for controlling the content of H2O and HF in the electrolyte, additives for improving low-temperature performance, and multifunctional additives.

[0040] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.

[0041] Example 1

[0042] 1) Preparation of negative electrode sheet:

[0043] The first negative electrode active material and the second negative electrode active material are mixed at a ratio of 7:3 to obtain a negative electrode active material, and the negative electrode active material, a binder styrene butadiene rubber and a dispersant sodium carboxymethyl cellulose are dissolved in deionized water at a weight ratio of 98:1:1, and the mixture is stirred and mixed to obtain a negative electrode slurry.

[0044] The negative electrode slurry is evenly coated on the current collector copper foil and dried to obtain the negative electrode sheet.

[0045] Among them, the first negative electrode active material is secondary particle graphite, the aspect ratio a of the first negative electrode active material is 1.5, the powder compaction pressure release rebound rate P1 is 10%, the surface oxygen content H1 is 5%, and the particle size Dv50 is 16μm; the second negative electrode active material is single particle graphite, the aspect ratio b of the second negative electrode active material is 5.0, the powder compaction pressure release rebound rate P2 is 10%, the surface oxygen content H2 is 3%, and the particle size Dv′50 is 10μm.

[0046] 2) Preparation of positive electrode:

[0047] The positive electrode active material NCM523, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 97:2:1, and the solvent NMP is added, and stirred under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0048] 3) Preparation of isolation membrane:

[0049] The isolation membrane base film is made of one of polyethylene base film, polypropylene base film, polypropylene / polyethylene / polypropylene composite base film, polyimide base film, polyvinylidene fluoride base film, polyethylene non-woven base film, polypropylene non-woven base film, and polyimide non-woven base film, and a first coating of vinylidene fluoride and ceramic particles and a second coating of styrene butadiene rubber and ceramic particles are coated on both sides of the diaphragm to make a diaphragm.

[0050] 4) Preparation of electrolyte:

[0051] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0052] 5) Battery preparation:

[0053] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then they are wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0054] The preparation methods of Examples 2 to 18 and Comparative Examples 1 to 14 are the same as that of Example 1, except for the composition and parameters of the first negative electrode active material and the second negative electrode active material, as shown in Table 1 below.

[0055] Test method:

[0056] (1) Surface oxygen content test: Six samples of the same active material were randomly selected and photographed at a magnification of 1500x using a scanning electron microscope (SEM) (GeminiSEM 560). EDS was then used to perform an elemental surface scan to obtain the oxygen content on the surface of the active material. The median of the data was taken as the oxygen content data H.

[0057] (2) Aspect ratio test: Six samples of the same active substance were randomly selected and photographed using a scanning electron microscope (SEM) (GeminiSEM 560) at a magnification of 3000x. The length and width of the particles in the electron microscope image were measured, and the aspect ratio was determined using the length / width ratio. The median of the measured data was taken as the aspect ratio of the active substance.

[0058] Table 1

[0059]

[0060]

[0061] Performance test: The lithium-ion batteries obtained in the examples and comparative examples were subjected to the following tests respectively. The test results are shown in Table 2 below.

[0062] (1) Liquid swelling performance test: After the capacity is divided, the thickness d1 of the battery cell is measured with 600PPG, and then the thickness d2 is fixed at a fixed position with a micrometer, r = (d1-d2) / d2; r < 2% means slight liquid swelling, 2% ≤ r ≤ 5% liquid swelling, r > 5% means severe liquid swelling.

[0063] (2) Energy density test: Energy density (Wh / kg) = discharge capacity (Wh) / mass of lithium-ion secondary battery (kg).

[0064] (3) Particle size test: The Dv90 of the negative electrode active material was measured using a laser diffraction particle size distribution measuring instrument (Malvern Mastersizer 3000) according to the particle size distribution laser diffraction method GB / T19077-2016 to obtain the Dv90.

[0065] (4) Powder compaction density test: compaction density meter (CARVER, USA), according to the graphite negative electrode material powder compaction test method GB / T24533-2019, record the 5T compaction density value PD1; after standing for 30 minutes, measure the powder pressing height again and calculate the compaction density PD2, the pressure relief rebound rate v = (PD1-PD2) / PD1.

[0066] (5) Hot box test: The fully charged battery cell is placed in an oven. The oven temperature is raised from 20±5℃ to 135±2℃ at a rate of 5±2℃ / min and maintained for 60 minutes before stopping. If the battery cell does not catch fire or explode after the test, it is considered to have passed the test.

[0067] Table 2

[0068]

[0069]

[0070] From the comparison of the results of Examples 1-18 and Comparative Examples 1-15 in Table 2 above, it can be seen that by controlling the aspect ratio of the first negative electrode active material and the second negative electrode active material and the powder compaction pressure relief rebound rate to satisfy the relationship: 37*P1 / a+75*P2 / b>2.5, the pores and compaction density between the negative electrode active material particles after rolling are ensured, while increasing the electrolyte penetration and reducing the swelling of the battery cell to achieve high energy density and good battery performance. By controlling the particle size and oxygen content of the first negative electrode active material and the second negative electrode active material to satisfy the relationship: H1*Dv50+235k*H2 / Dv50<1.85, it is ensured that the battery has high energy density while also having high safety performance, reducing the hot box safety performance caused by the violent side reactions in the battery cell.

[0071] Comparison of the data of Examples 1, 8-9 and Comparative Examples 11-12 shows that when the aspect ratio of the second negative electrode active material decreases, the flake characteristics of the particles are weakened, which is not conducive to slippage during rolling, resulting in a decrease in compaction density. When it is less than the preset range, the flake structure is not obvious and the energy density is low. When it exceeds the preset range, the flake structure is obvious, slippage occurs after rolling, the particles are more densely packed, and the liquid swelling is obvious.

[0072] Comparison of the data of Examples 1, 6-7 and Comparative Example 4 shows that when the aspect ratio of the first negative electrode active material is less than the preset range, the sheet structure is not obvious and the energy density is low. When it exceeds the preset range, the sheet structure is obvious, the sheet structure slips after rolling, the particles are more densely packed, and the liquid swelling is obvious.

[0073] From the data comparison of Examples 1, 10-11, 14 and Comparative Examples 7, 13, it can be seen that when the surface oxygen content of the negative electrode active material is high, the etching degree is high, more low-crystalline components are removed, the material capacity and compaction density increase, and thus the energy density increases. When it exceeds the preset range, the high temperature instability will increase.

[0074] From the data comparison of Examples 1, 12-13 and Comparative Example 14, it can be seen that when the proportion k of the second negative electrode active material decreases, the packing density of the active material particles decreases and the energy density decreases. When it exceeds the preset range, the proportion of the sheet-like second negative electrode active material increases and the degree of liquid swelling increases.

[0075] From the data comparison of Examples 1, 15-16 and Comparative Example 3, it can be seen that when the particle size of the first negative electrode active material is small, the degree of granulation is small, the amount of binder is reduced, and the capacity compaction loss is small. Since the binder introduced by granulation has a slightly poorer thermal stability than the graphite itself, when the particle size of the first negative electrode active material exceeds the preset range, the stability of the overall active material will deteriorate.

[0076] From the data comparison of Examples 1, 17-18 and Comparative Examples 2, 14, it can be seen that when the particle size of the second negative electrode active material is small, the material capacity per gram is reduced, the specific surface area is large, and the side reactions increase, resulting in poor high temperature performance. When it is less than the preset range, the etching degree of the second negative electrode active material and the first negative electrode active material is high, and the particle size of the second negative electrode active material is small, which will cause violent side reactions, thereby seriously deteriorating the hot box. When it exceeds the preset range, the particle size of the second negative electrode active material is small, and the degree of oxidation is deep, which will increase the instability of high temperature.

[0077] From the data comparison of Example 1 and Comparative Examples 1-2, it can be seen that when the pressure release rebound is low and the aspect ratio of the second negative electrode active material to the first negative electrode active material is large, the electrolyte is difficult to penetrate, resulting in liquid swelling. When the etching degree of the second negative electrode active material and the first negative electrode active material is high and the particle size of the second negative electrode active material is small, a violent side reaction will be triggered, thereby seriously deteriorating the hot box.

[0078] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A negative electrode material, characterized in that: including a first negative electrode active material and a second negative electrode active material; The aspect ratio of the first negative electrode active material is a, and the powder compaction pressure release rebound rate is P1; the aspect ratio of the second negative electrode active material is b, and the powder compaction pressure release rebound rate is P2; wherein P1, P2, a and b satisfy the relationship: (37*P1 / a+75*P2 / b)>2.

5.

2. A negative electrode material according to claim 1, characterized in that: The aspect ratio a of the first negative electrode active material is 1<a≤3, and the aspect ratio b of the second negative electrode active material is 3≤b<5.

3. A negative electrode material according to claim 1, characterized in that: The compression and decompression rebound rate P1 of the first negative electrode active material powder is 10%-15%, and the compression and decompression rebound rate P2 of the second negative electrode active material powder is 6%-10%.

4. A negative electrode material according to claim 1, characterized in that: The particle size of the first negative electrode active material is Dv50, and the surface oxygen content is H1; the particle size of the second negative electrode active material is Dv′50, and the surface oxygen content is H2, and the mass of the second negative electrode active material accounts for k of the total mass of the negative electrode material; wherein Dv50, Dv′50, H1, H2 and k satisfy the relationship: (H1*Dv50+235k*H2 / Dv50)<1.

85.

5. A negative electrode material according to claim 4, characterized in that: The mass of the second negative electrode active material accounts for 10%-30% of the total mass k of the negative electrode material.

6. A negative electrode material according to claim 4, characterized in that: The surface oxygen content H1 of the first negative electrode active material is 5%-10%, and the surface oxygen content H2 of the second negative electrode active material is 0%-3%.

7. A negative electrode material according to claim 4, characterized in that: The particle size Dv50 of the first negative electrode active material is 10-16 μm, and the particle size Dv′50 of the second negative electrode active material is 6-10 μm.

8. A negative electrode material according to claim 1, characterized in that: The negative electrode active material includes one or more of natural graphite and artificial graphite.

9. A negative electrode sheet, characterized in that: The negative electrode material comprises the negative electrode material according to any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: Including the negative electrode sheet as claimed in claim 9.